Wrap and cap: prevention of admission hypothermia in very low birth weight infants in a resource restricted hospital: a pilot study. - Jones, Thomas Ryan (Stellenbosch : Stellenbosch University, 2023)
Thesis (MPhil)--Stellenbosch University, 2023.